Effects of Sugar Cane Expansion in Southeastern Mato Grosso do Sul and Possible Pathways Towards a Sustainable Agenda (Sustainability in Debate, 2014)
The Brazilian Alcohol program (Pró-Álcool) is pointed out as a sustainable development tool.However, the negative impacts produced throughout its production can minimize its benefits. Inrecent years, the area under sugar cane increased from 105 thousands hectares to more than700 thousands hectares in the state of Mato Grosso do Sul. Nonetheless, little is known about theimpacts faced by this region of Brazil. The goal of this project was to evaluate the sugarcaneimpacts in the Southwestern region of that state, through interviews, reports analysis and in locovisits. The better protection of Areas Legally Protected and the incensement in the number ofenterprises formally registered are within the positive effects. Related to the negative impacts,stands out conflicts related to Indigenous Lands and issues related to the public health system inthe cities analysed. The results point out the need, for the public governments create andcoordinate actions, alongside other sectors, with clear statements focused on the sustainabledevelopment.